(untitled) (Journal of Plant Disease Sciences, 2023)
A field trial was carried out in Parbhani to validate the technology for managing soil-borne and seed-borne safflower diseases. The purpose of the trial wasto compare farmer practices with the strain (Th4d) used as a seed dresser. Before seed was sown, it was treated with the fungicides Carbendazim 12 % +Mancozeb 63 % @ 0.2 % and . In comparison to farmers’ Trichoderma harzianum practices, where the disease incidence was 11.3 %, the seed treatments harzianum Trichoderma harzianum Trichoderma Th4d SC @ 2ml/kg and Th4d WP @ 10g/kg were found to be the most effective, with much lower incidence of seed/soil transmitted disease at 5.3%.The highest seed yields (1034 kg/ha and 1055 kg/ha) were likewise reported by the treatments Th4d SC @2ml/kg and Trichoderma harzianum